Le travail caché du prisonnier entre « littérature » et « politique ». Quelques réflexions sur les « sources » des Cahiers de prison d’Antonio Gramsci - Fabio Frosini (Laboratoire Italien)
The present contribution brings into focus the nexus between self-censorship and political analysis of the world as it was at the time of the Prison Notebooks. After a brief presentation of the way in which self-censorship has been evaluated and analysed in the studies and editions of Gramsci, we attempt to reconstruct a number of segments of the Notebooks, in which Gramsci carries out critical analyses of the world of the time in connection with a political project of a thoroughgoing redefinition of the PCI’s political strategy. The point to which we direct most attention is that group of processes that, briefly and somewhat conventionally Gramsci defines as “Americanism and Fordism”. We demonstrate the nexus between this group of phenomena and his investigation of the crisis and the transformation of parliamentarism, that is to say of the emergence of a “corporative” society, even outside fascist Italy, and of the appearance of a new form of politics, in which the masses are completely organized and actively present within the organizations created by the State in order to control them.